A STUDY OF HOW DAILY MIGRANT WAGE LABORERS AFFECT SOCIAL COHESION WITH IN COMMUNITIES - Shigufta Nazneen (International Journal of Multidisciplinary Research and Studies, 2021)
One of the most critical issues that the member states of the ropean Union are now attempting to overcome is the assimilation of migrant labour. This is especially true as the continues to increase in cultural and political variety. Specifically, the eastward enlargement in 2004 to include eight post-communist countries from Eastern rope raised fears that economic migration might undermine perceived social cohesion within the member states. This fear was fueled by the fact that the enlargement occurred in 2004. At the same time, the possibility of additional eastern enlargements makes the topic of the relationship between the growth of membership and the incorporation of new migrant groups an ongoing issue that is of a very high level of relevance, particularly in the urban areas that are located outside of the "rope of cities" (Harding, 1997). A increasing body of academic research investigates the perspectives of different ropean nations on one another as well as the ways in which immigration impacts the formation of a pan-ropean identity (Laffan, 1996). Scholarly attention is also being paid increasingly to the experiences of migrants from the eight Accession (A8) countries within host countries, as well as the role that local governments play in the process of economic incorporation for migrants.